EFFORTS TO BULDING LOCAL WISDOM IN CHRACTER EDUCATION IN ELEMENTARY SCHOOL (International Conference on Elementary Education, 2018)
In an effort to build local wisdom in character education in elementary school is very less effective. That is the number of students who do not understand what local wisdom is and the lack of students in remembering culture in each region, therefore a research is needed in which students in primary schools can foster local wisdom and can foster the character of every regional culture in Indonesia . So in this paper an exploration of the literature and references of the literature that presents local wisdom is carried out. The exploration results will be described in the form of a summary of the problems and solutions outlined by several researchers in the review literature. It is hoped that readers can build local wisdom in character education at school and can apply it in school or in everyday life.